PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS “PAPI PROTOTUM” SEBAGAI INOVASI PEMBELAJARAN PADA MATERI PROSES FOTOSINTESIS TUMBUHAN UNTUK SISWA KELAS 4 SDN KRATON - Natalia, Sofia; Mukmin, Bagus Amirul; Putri, Kharisma Eka (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This study aims to: (1) How is the validity of interactive multimedia based on papi prototum on the material of plant photosynthesis process (2) How is the practicality of interactive multimedia based on papi prototum on the material of plant photosynthesis process. The study was conducted on 17 students of grade IV of SDN Kraton. This study used the Research and Development (R&D) model with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. The media development process was carried out systematically according to the ADDIE stages to produce valid, practical and effective learning media. The results of the three aspects obtained a result of 90.5% which is included in the "very valid" category. Therefore, media based on "papi prototum" is suitable for use in the science learning process in elementary schools as a means to increase student involvement, facilitate understanding of abstract material, and support the achievement of basic competencies optimally. The validation results by material experts and media experts obtained scores of 90% and 89% respectively, indicating that the media is very valid and suitable for use. Practicality test through questionnaires given to teachers and students produced scores of 91% and 86%, indicating that the media is very practical. Based on the data from the validity and practicality tests, it can be concluded that interactive multimedia based on papi prototum on the material of plant photosynthesis process is valid and practical to use.